FINANCE INNOVATION IN THE PROCESS OF DIGITAL ECONOMY TRANSFORMATION - D. I. Filippov (Plekhanov Russian University of Economics, 2018)
Finance innovation is essential for efficient functioning of finance market and passing-over to digital economy. Digital technologies reform work methods of state bodies, companies, entrepreneurs and citizens making their objectives easier. Digital innovation stimulates the development of digital economy and society, provides an opportunity to use new achievements in different fields and causes transformation of economy. Companies with the high level of organizational and human capital can get the highest profits from investment in digital technologies. These companies are rather flexible and are able to maximize benefits from their investment through finding and using possibilities for sales growth, process reorganization and production efficiency rising. In these circumstances the key driver of the process of passing-over to digital economy is finance innovation. The article shows historical preconditions of the phenomenon, i.e. digital economy rising and offers the author’s definition. The author classifies basic factors affecting the process of digital economy development and puts forward the channels of raising companies’ productivity through investment into digital technologies, which leads to digital transformation of business.